Fuzzy Linear Programming Dalam Optimalisasi Pelayanan Air Bersih Perusahaan Daerah Air Minum (PDAM) Kab. Jeneponto Menggunakan Metode Sabiha - Wahidah Sanusi; Sukarna; Irham Aryandi Basir (Jurusan Matematika FMIPA UNM, 2020)
Linear fuzzy programing is advance model for linear programing to determin the optimal result that contains fuzzy numbers. Linear Fuzzy programing can be solved using Sabiha’s method. Which is based on real linear fuzzy numbers in triplet numbers form. This paper used linear fuzzy programming model and Sabiha’s method, to determin the optimal solution on PDAM Kab. Jeneponto’s operation plan. Each indicator constructed to optimized objective function and constraint function. Results of this research have optimal solution for each objective variable was obtained with an optimal value for total costumer are 9075,999999999990 from 8896,999999999990 the type of household customer, 96,0000000000112 the type of special social customer, and 82,9999999999982 the type of public social costumer. With an optimal total revenue Rp. 4,753,125,000 and total water demand 1,082,303 m3.